2020
DOI: 10.1530/erp-20-0017
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic value of Tei index in acute myocardial infarction: a systematic review

Abstract: Background: Echocardiographic evaluation of left ventricular ejection fraction (LVEF) is used in the risk stratification of patients with an acute myocardial infarction (AMI). However, the prognostic value of the Tei index, an alternative measure of global cardiac function, in AMI patients is not well established. Methods: We conducted a systematic review, using MEDLINE and EMBASE, to evaluate the prognostic value of the Tei index in predicting adverse outcomes in patients presenting with AMI. The data was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…In previous studies, the TI was identified as a sensitive tool for diagnosis and risk stratification of patients with heart failure [ 16 , 23 , 24 ], chronic coronary syndrome [ 19 ] and acute myocardial infarction [ 25 , 26 ]. However, despite the promising findings of previous studies, evidence on the clinical aspects of the TI in myocarditis is very scarce.…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, the TI was identified as a sensitive tool for diagnosis and risk stratification of patients with heart failure [ 16 , 23 , 24 ], chronic coronary syndrome [ 19 ] and acute myocardial infarction [ 25 , 26 ]. However, despite the promising findings of previous studies, evidence on the clinical aspects of the TI in myocarditis is very scarce.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, Rahman N. and co-authors (2009) showed that the TEI index value > 0.40 had better sensitivity (86% vs. 65%), specificity (82% vs. 50%) and accuracy (83% vs. 58%) compared with LV EF <40% to predict cardiac complications, including cardiogenic shock, revascularization, rehospitalization, congestive heart failure, and atrioventricular block [11].…”
Section: Introductionmentioning
confidence: 99%
“…Souza L.P. et al (2011) found that LV EF ≤45% was associated with an increased chance of heart failure progression, but only among patients ≥ 60 years of age with a TEI index ≥ 0.57. Biering Sørensen T. et al (2013) reported that TEI index values greater than (0.59 ± 0.16 vs. 0.52 ± 0.13, P <0.001) was associated with major adverse events, including congestive heart failure, myocardial infarction, and mortality [11].…”
Section: Introductionmentioning
confidence: 99%
“…Several echocardiographic time intervals and parameters are associated with cardiac performance, thus with clinical outcomes (13)(14)(15)(16)). Tei's index, which is defined as the sum of isovolumic contraction time and relaxation time divided by the ejection time, is described as an index of global myocardial performance and as a prognostic factor in patients presenting with acute myocardial infarction (17). The isovolumic time/heterovolumic time ratio (I/H) index, which is defined as the sum of isovolumic relaxation and contraction time divided by the sum of ejection and filling time, has also been considered a potential indicator of myocardial time yield and efficiency (18).…”
Section: Introductionmentioning
confidence: 99%